TANGGUNG JAWAB HUKUM PERUSAHAAN YANG BERGERAK DI BIDANG AGGREGATOR BACA BERITA INDONESIA (BaBe) YANG DIAMBIL DARI PENYEDIA KONTEN - Tri Ditrarini Saraswati, - (2019)
Companies engaged in the aggregator is the company that collects content from content providers namely web or other applications from online sources that are in Indonesia or outside Indonesia and then distributed back to the community. In this thesis, the author focuses research to the news aggregator. Unlike a press company, the content that is in the application of this aggregator of news not selfproduced through journalists, but getting the content from the content providers. The issue arose in the delivery of information in the content of a news aggregator rated by the community is less obvious, leading to ambiguous, even a hoax. Because only a press company that can attract the requested against his announcement with reference to Undang-Undang Number 40 Years 1999 about the press and journalistic code of ethics. On the research of this thesis, the author will also take examples of companies engaged in the aggregator Baca Berita Indonesia (BaBe). Application of BaBe Indonesia is an application owned by PT Mainspring Technology, which can be found news content or non portal from various news sources in Indonesia. In the application there is a statement that BaBe Indonesia will unleash itself from any liabilities, claims arising out of or in connection with content providers. The company also will not be a party to the dispute or negotiation between readers with content providers, It is as stated in the user agreement on the application of BaBe Indonesia. So in this thesis, the author will discuss about user agreement made by companies engaged in the aggregator and his responsibilities